2015
DOI: 10.1111/bcpt.12432
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Truncating AUC at 12, 24 and 48 hr When Evaluating the Bioequivalence of Drugs with a Long Half‐Life

Abstract: Bioequivalence studies of drugs with a long half-life require long periods of time for pharmacokinetic sampling. The latest update of the European guideline allows the area under the curve (AUC) truncated at 72 hr to be used as an alternative to AUC 0-t as the primary parameter. The objective of this study was to evaluate the effect of truncating the AUC at 48, 24 and 12 hr on the acceptance of the bioequivalence criterion as compared with truncation at 72 hr in bioequivalence trials. The effect of truncated A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…For small molecules with a long elimination half‐life, it is well‐accepted to use tAUC in lieu of AUC 0–inf , given that the tAUC can cover the complete absorption phase 7 . The utility of tAUC has also been demonstrated in several clinical and modeling and simulation studies of small‐molecule drugs 45–51 . Our study demonstrated that to bridge the PFS and AI , tAUC evaluated until day 28 post‐dose can achieve high concordance (≥85%) for biologics that exhibit linear or nonlinear elimination with k a values greater than or equal to 0.1/day and with a typical sample size of 70 subjects per arm.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…For small molecules with a long elimination half‐life, it is well‐accepted to use tAUC in lieu of AUC 0–inf , given that the tAUC can cover the complete absorption phase 7 . The utility of tAUC has also been demonstrated in several clinical and modeling and simulation studies of small‐molecule drugs 45–51 . Our study demonstrated that to bridge the PFS and AI , tAUC evaluated until day 28 post‐dose can achieve high concordance (≥85%) for biologics that exhibit linear or nonlinear elimination with k a values greater than or equal to 0.1/day and with a typical sample size of 70 subjects per arm.…”
Section: Discussionmentioning
confidence: 55%
“…7 The utility of tAUC has also been demonstrated in several clinical and modeling and simulation studies of smallmolecule drugs. [45][46][47][48][49][50][51] Our study demonstrated that to bridge the PFS and AI , tAUC evaluated until day 28 post-dose can achieve high concordance (≥85%) for biologics that exhibit linear or nonlinear elimination with k a values greater than or equal to 0.1/day and with a typical sample size of 70 subjects per arm. tAUC 0-28 could be used appropriately to evaluate PK comparability between the two presentations, even for biologics with a long elimination half-life of 40 days, to reduce the study duration compared with an evaluation of AUC 0-inf .…”
Section: Discussionmentioning
confidence: 73%